2013
DOI: 10.1101/cshperspect.a020735
|View full text |Cite
|
Sign up to set email alerts
|

The Spatiotemporal Organization of ErbB Receptors: Insights from Microscopy

Abstract: Signal transduction is regulated by protein-protein interactions. In the case of the ErbB family of receptor tyrosine kinases (RTKs), the precise nature of these interactions remains a topic of debate. In this review, we describe state-of-the-art imaging techniques that are providing new details into receptor dynamics, clustering, and interactions. We present the general principles of these techniques, their limitations, and the unique observations they provide about ErbB spatiotemporal organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 63 publications
0
28
0
Order By: Relevance
“…Other techniques, for example, cryo TEM, are needed to study the protein structure, and the cellular ultrastructure 15 . Secondly, studying the dynamic interplay of a multiple of proteins in live cell in time-lapse microscope is not feasible on account of radiation damage, and requires state-of-the-art light microscopy 23 .…”
Section: Representative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other techniques, for example, cryo TEM, are needed to study the protein structure, and the cellular ultrastructure 15 . Secondly, studying the dynamic interplay of a multiple of proteins in live cell in time-lapse microscope is not feasible on account of radiation damage, and requires state-of-the-art light microscopy 23 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…Studying the spatial arrangement of this membrane receptor in whole cells provides important context information about its function and possible changes thereof [11][12][13][14] . But it remains challenging to probe the distribution of EGFR monomers, dimers, and clusters directly on a (sub-)cellular level with biochemical-or conventional microscopy methods 15 . Our method is capable of visualizing EGFRs with a spatial resolution of a few nanometers such that the locations of proteins in a complex can be determined.…”
Section: Introductionmentioning
confidence: 99%
“…This model has been supported by crystal structures of the extracellular domain of EGFR (7,8) as well as by reports of EGFR dimerization after stimulation with EGF. However, numerous studies have also reported the presence of EGFR dimers or even larger oligomers in the membranes of resting cells (9)(10)(11)(12)(13). The presence of preformed EGFR dimers and oligomers indicates that regulation of EGFR signaling is more complex than implied by the model outlined above (Fig.…”
Section: Introductionmentioning
confidence: 92%
“…The existence of preformed dimers, their relative amount in resting cells, and their role in EGFR signaling continue to present open questions and the findings of individual studies differ considerably (9,14). While some authors report negligible amounts of preformed dimers (15), others have found most EGFR molecules in dimeric form (6,9,16,17). Nagy et al (18) observed preformed dimers only at high expression levels of EGFR of ~600,000 receptors per cell.…”
Section: Introductionmentioning
confidence: 99%
“…and lead to decisions triggering distinct signalling pathway/s is incompletely understood (Bessman et al, 2014;Valley et al, 2014). A key challenge…”
Section: Introductionmentioning
confidence: 99%